Apistogramma eleutheria and A. Flavipedunculata, two new species of dwarf cichlids from the rio Curuá on Serra do Cachimbo, Brazil (Teleostei: Cichlidae) - Varella, Henrique R.; Britzke, Ricardo [UNESP] (My University, 2016)
Apistogramma eleutheria and Apistogramma flavipedunculata are described from the upper portion of two adjacent tributaries of the rio Curua on the Serra do Cachimbo. Apistogramma eleutheria, new species, is isolated from the lower portion of rio Treze de Maio (a tributary of the middle rio Curua), by a waterfall with same name. It is similar to several species of the A. regani species group, but differs by the coloration of brooding females. Brooding females of A. eleutheria have a very dark, blackish pigmentation on the median area of gular region occupying the ventral portion of opercular series and branchiostegal membranes, which is most similar to that found in females of A. kullanderi. In A. kullanderi, however, the dark gular pigmentation is more expansive, extending onto the ventral half of the head, and continuing posteriorly onto belly and along anal-fin base. Apistogramma flavipedunculata, new species, is only known from the rio Escorpiao, and is probably isolated in the upper rio Curua by a series of three waterfalls. It is distinguished by the unique color pattern of adult males, which have the posterior part of the flank and caudal peduncle dominated by a light yellow pigmentation, which results in a dark midlateral band fragmented posteriorly and dark bars masked or absent (though present in juveniles); also differing from all congeners except A. luelingi and A. eleutheria by having exclusively four anal-fin spines instead of three.